Algorithm Theory -- SWAT 2012 13th Scandinavian Symposium and Workshops, Helsinki, Finland, July 4-6, 2012, Proceedings - Fomin, Fedor V.; Fomin, Fedor V.; Kaski, Petteri.; Kaski, Petteri. (Theoretical Computer Science and General Issues, 2012)
This book constitutes the refereed proceedings of the 13th International Scandinavian Symposium and Workshops on Algorithm Theory, SWAT 2012, held in Helsinki, Finland, in July 2012, co-located with the 23rd Annual Symposium on Combinatorial Pattern Matching, CPM 2012. The 34 papers were carefully reviewed and selected from a total of 127 submissions. The papers present original research and cover a wide range of topics in the field of design and analysis of algorithms and data structures.